2021
DOI: 10.3389/fpls.2021.732867
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Sucrose to Starch Metabolism Is Related to the Initiation of Inferior Grain Filling in Large Panicle Rice

Abstract: The poor grain-filling initiation often causes the poor development of inferior spikelets (IS) which limits the yield potential of large panicle rice (Oryza sativa L.). However, it remains unclear why IS often has poor grain-filling initiation. In addressing this problem, this study conducted a field experiment involving two large panicle rice varieties, namely CJ03 and W1844, in way of removing the superior spikelets (SS) during flowering to force enough photosynthate transport to the IS. The results of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 75 publications
4
29
0
Order By: Relevance
“…Furthermore, compared with CJ and HI, the advantage that EJIH has in spikelets per panicle was detected in all six positions of the panicle, especially for US and MS (Table 5), implying that it was an effective way to promote panicle size from increasing grains positioned in the US and MS. In this study, EJIH had a similar filled-grain percentage relative to CJ and HI (Table 4) and did not exhibit the grain-filling barrier that has previously been found in japonica/indica hybrids [33,34]. From this, it can be deduced that progress has been made in developing japonica/indica hybrids with better grain-filling efficiency in China [8,25].…”
Section: Discussionsupporting
confidence: 68%
“…Furthermore, compared with CJ and HI, the advantage that EJIH has in spikelets per panicle was detected in all six positions of the panicle, especially for US and MS (Table 5), implying that it was an effective way to promote panicle size from increasing grains positioned in the US and MS. In this study, EJIH had a similar filled-grain percentage relative to CJ and HI (Table 4) and did not exhibit the grain-filling barrier that has previously been found in japonica/indica hybrids [33,34]. From this, it can be deduced that progress has been made in developing japonica/indica hybrids with better grain-filling efficiency in China [8,25].…”
Section: Discussionsupporting
confidence: 68%
“…Phenylpropanoid which was a rich source of secondary metabolites in plants, together with plant hormone, played important roles in plant growth, development, and defense ( Desmedt et al, 2021 ; Dong and Lin, 2021 ). Moreover, starch and sucrose metabolism was the vital pathway in the process of rice grain filling, which could finally affect the yield ( Fan et al, 2019 ; Jiang et al, 2021 ; Mathan et al, 2021 ). All these information indicated that DXWR probably had superior disease-resistance and starch synthesis ability.…”
Section: Discussionmentioning
confidence: 99%
“…Negative correlation has been found between levels of ethylene in developing seeds and enzymatic activities linked with starch metabolism eventually leading to poor grain filling, for instance more ethylene levels in developing seeds leads to poor grain filling (Zhang et al, 2009). A detailed description of the metabolic pathways associated with sucrose to starch conversion in developing grain particularly during grain filling stage was recently reported by Jiang et al (2021). Comparative genomics study through transcriptome profiling among two rice genotypes under mild drought during grain-filling stage was conducted by Liang et al (2021) and in a suppressed transgenic line of the OsSYT-5 gene, Shanmugam et al (2021) reported the enhanced photosynthetic rate with reduced stomatal conductance and transpiration under water deficit condition.…”
Section: Grain Filling In Ricementioning
confidence: 98%